Self-assessment of Knowledge vs. Real Reactions in Simulated Emergency Situations among Contact Lens Wearers in Switzerland - Perschak, Philipp; Said, Sadiq; Metzler, Simone; Zweifel, Sandrine; Barthelmes, Daniel; Hermann, Dominique; Herrmann, Didier; Hafezi, Farhad; Kollros, Léonard; Bosch, Martina Monika; Blaser, Frank (Klinische Monatsblätter für Augenheilkunde, 2025)
Background If used properly, contact lenses (CLs) provide a safe and effective alternative to eyeglasses for refractive error correction. However, often due to patient noncompliance, CL-related complications may occur, such as discomfort, dry eye, as well as serious conditions like infectious keratitis. Our study aimed to assess the perceived knowledge and behavior of CL wearers in Switzerland regarding the handling of CLs and associated ocular health risks.Methods This investigator-initiated, cross-sectional, qualitative, multicenter study was conducted in Switzerland from August 2023 to August 2024. After verbal consent, CL wearers were interviewed using a structured survey. The questionnaire explored participantsʼ demographics, their perceived knowledge of the overall handling of CLs and associated health risks, as well as their behavior in two emergency scenarios involving monocular redness or pain. The descriptive statistical analysis was performed using Microsoft Excel (Microsoft Corp., Redmond, WA, USA). Figures were created with Prism version 10.2.3 (GraphPad Software, San Francisco, CA, USA).Results A total of 172 participants with a median (IQR [range]) age of 39 (27 to 54 [10 to 82]) years were interviewed, whereby 81 (47.1%) were female. Myopia (61.0%) and keratoconus (30.2%) were the most reported indications for CL use. In terms of overall CL handling, 91.3% of participants felt well or sufficiently informed, whereas this was the case of 66.3% regarding CL-related health risks. In the scenario involving eye redness during CL use, 135 of 175 (77.1%) responses did not mention seeking professional advice, while 25 (14.3%) indicated visiting an ophthalmologist within 1 day of symptom onset. In the event of monocular pain, 67 of 179 (37.4%) responses did not consider seeking professional care, whereas 86 (48.0%) included consulting an ophthalmologist.Conclusion This study provides insight into the unmet educational need of CL wearers, especially regarding CL-related complications. Participants generally felt better informed about overall CL handling than about the potential health risks. This information discrepancy is reflected by their responses to scenarios involving monocular redness or pain, where a considerable number of participants failed to react adequately. Further studies are warranted to explore effective, practical strategies for improving patient awareness and behavior.
Keywords: contact lenses; questionnaire; infectious keratitis; patient behavior; patient education